(untitled) (Estudios Humanísticos. Historia, 2002)
El propósito de este artículo es estudiar los epitafios del siglo XIII y XIV que se encuentran reaporvechados en la bóveda del locutorio del monasterio de Santa María de Osera. Estos epitafios han sido estudiados en su génesis, en su forma, en su tradición y en su evolución. Es decir, pretendemos conocer al autor material formal de cada una de estas inscripciones, saber qué les llevó a ejecutarlas, cuál era su funcionalidad, quién era su destinatario, reconstruir el proceso de ejecución de los epígrafes y conocer las visicitudes por las que han atravesado a lo largo del tiempo. Abstract The purpose of this article is to study the epitaphs of the 13th and 14th centuries, which have been dept on the vault of the "locutorio" in the monastery of Saint Maria of Osera. Therefore, we have studied the genesis, form, tradition and evolution of the epitaphs. That is to say, our purpose is to know the material and formal authors of each of these inscriptions, to find out what lead them to produce them, and what functions the inscriptions had, further, we are interested in the addressee of the epitaphs, as well as in reconstructing the process of production of the epigraphs, and in examining the difficulties they went through with the passing of time.